The effects, underlying mechanism and interactions of dexamethasone exposure during pregnancy on maternal bile acid metabolism. (10th October 2020) - Fang, Man; Zhang, Qi; Yu, Pengxia; Ge, Caiyun; Guo, Juanjuan; Zhang, Yuanzhen; Wang, Hui
Highlights: Dexamethasone exposure during pregnancy induced maternal ICP. Dexamethasone exposure during pregnancy disordered the hepatic bile acid metabolism. Estrogen and nuclear receptors participated in the pathogenesis. There were interactions between pregnancy status and dexamethasone exposure. Abstract: As important members in steroids related signal pathways, bile acids are very important in regulating substance metabolism and immune homeostasis. However, bile acids are highly cytotoxic, and the excessive accumulation can induce several abnormalities such as cholestatic liver injury. It is known that the bile acid metabolism alters during pregnancy and mostly will not result in pathologies. However, the effect of dexamethasone exposure during pregnancy on bile acid metabolism is still unknown. In this study, pregnant Wistar rats were subcutaneously administered dexamethasone (0.2 mg/kg.d) or saline from gestation day 9–21, while virgin rats were given the same treatment for 13 days. We found that, physiological pregnancy or dexamethasone exposure during non-pregnancy did not affect maternal serum TBA level and liver function. Nevertheless, dexamethasone exposure during pregnancy increased serum TBA level and accompanied with liver injury. Furthermore, we discovered that the conservation of bile acid homeostasis under pregnancy or dexamethasone exposure was maintained through compensatory pathways. However, dexamethasone exposure during pregnancy tipped the balance of liver bile acid homeostasis by increasing classical synthesis and decreasing efflux and uptake. In addition, dexamethasone exposure during pregnancy also increased serum estrogen level and nuclear receptors mRNA expression levels. Finally, two-way ANOVA analysis showed that dexamethasone exposure during pregnancy could induce or facilitate maternal cholestasis and liver injury by up-regulating ERα and CYP7A1 expression. This study confirmed that dexamethasone exposure during pregnancy was related to maternal intrahepatic cholestasis of pregnancy and should be carefully monitored in clinical settings.